2015
DOI: 10.1016/j.neuron.2015.01.024
|View full text |Cite|
|
Sign up to set email alerts
|

RIM-Binding Protein Links Synaptic Homeostasis to the Stabilization and Replenishment of High Release Probability Vesicles

Abstract: Here we define activities of RIM-Binding Protein (RBP) that are essential for baseline neurotransmission and presynaptic homeostatic plasticity. At baseline, rbp mutants have a ~10-fold decrease in the apparent Ca2+ sensitivity of release that we attribute to 1) impaired presynaptic Ca2+ influx, 2) looser coupling of vesicles to Ca2+ influx and 3) limited access to the readily-releasable vesicle pool (RRP). During homeostatic plasticity, RBP is necessary for the potentiation of Ca2+ influx and the expansion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
133
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(144 citation statements)
references
References 36 publications
11
133
0
Order By: Relevance
“…An independent study made a similar observation, showing that reduced Ca V 2.1 channel abundance and a correlated ~50% decrease in single action potential (AP) induced calcium influx, did not impair the rapid induction of presynaptic homeostasis (Gavino et al, 2015). Third, synaptic homeostasis is fully expressed over a 50-fold range of extracelluar calcium concentration (0.3 to 15mM [Ca 2+ ] e ) (Muller et al, 2015), arguing that the absolute amount of calcium influx per action potential does not influence the homeostatic modulation of presynaptic neurotransmitter release. Here, we confirm this finding in the α2δ-3 mutant background.…”
Section: Resultsmentioning
confidence: 99%
“…An independent study made a similar observation, showing that reduced Ca V 2.1 channel abundance and a correlated ~50% decrease in single action potential (AP) induced calcium influx, did not impair the rapid induction of presynaptic homeostasis (Gavino et al, 2015). Third, synaptic homeostasis is fully expressed over a 50-fold range of extracelluar calcium concentration (0.3 to 15mM [Ca 2+ ] e ) (Muller et al, 2015), arguing that the absolute amount of calcium influx per action potential does not influence the homeostatic modulation of presynaptic neurotransmitter release. Here, we confirm this finding in the α2δ-3 mutant background.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Acuna et al (8) showed that deletion of RIM-BP1 and RIM-BP2 in the murine Calyx of Held impairs the reliability of evoked neurotransmitter release, presumably due to an uncoupling of Ca V s from release sites. At the Drosophila NMJ, the RIM-BP ortholog DRBP, together with Bruchpilot, is an AZ core component, and elimination of DRBP causes severe structural deficits in AZ organization, associated with strongly impaired basal transmission and STP (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila homolog of RIM-binding proteins (DRBP) is indeed crucial for neurotransmitter release at the AZ of neuromuscular junctions (NMJs) because loss of DRBP reduces Ca V abundance and impairs the integrity of the AZ scaffold (6). DRBP-deficient flies show severe impairment of neurotransmitter release along with increased short-term facilitation (6,7).…”
mentioning
confidence: 99%
“…There appear to be a core set of genes necessary for both acute and chronic PHP expression, including ones involved in the homeostatic modulation of synaptic vesicle trafficking, presynaptic excitability, calcium channel activity, and active zone remodeling (Dickman and Davis, 2009; Frank et al, 2006; Muller et al, 2015; Younger et al, 2013). However, other genes appear to be dispensable for this core program, and may rather be involved in secondary functions, such as maintaining PHP expression over chronic time scales or supporting other aspects of homeostatic adaptation (Frank et al, 2009; Penney et al, 2012; Penney et al, 2016; Spring et al, 2016; Tsurudome et al, 2010).…”
Section: Discussionmentioning
confidence: 99%